2020
DOI: 10.1177/2156869320929386
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationship Quality and Suicidal Ideation in Young Adulthood

Abstract: Sociological research on suicidal ideation has often focused on structural factors, such as marital status, when analyzing the protective effects of social integration; however, less is known about how the quality of romantic relationships shapes suicidality among young adults. This study uses the National Longitudinal Study of Adolescent to Adult Health to examine the association between romantic relationship quality and suicidal ideation in young adulthood. Results indicate that simply being in a romantic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…The findings of this study are consistent with those of 52 who discovered that there is no direct association between family impact (marital conflict) and mental wellbeing. Furthermore, the findings of this study contradict those of [41][42][43][44][45][46][47] who discovered a direct association between these two factors. This study's findings are also in line with those of, 3,33,49,50 who found that family impact on coping and coping with strain are linked.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are consistent with those of 52 who discovered that there is no direct association between family impact (marital conflict) and mental wellbeing. Furthermore, the findings of this study contradict those of [41][42][43][44][45][46][47] who discovered a direct association between these two factors. This study's findings are also in line with those of, 3,33,49,50 who found that family impact on coping and coping with strain are linked.…”
Section: Discussioncontrasting
confidence: 99%
“…[38][39][40] Numerous previous studies have examined the relationship between family impact such as marital conflict and various aspects of wellbeing. The majority of previous research has established a direct link between marital conflict and aspects of life quality, such as mental health, [41][42][43][44] subjective wellbeing, 45 life satisfaction 46 and suicide ideation. 44,47 However, 48 study contradicts the findings of other researchers, as he discovered that marital conflict has no significant relationship with psychological wellbeing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies conceptualize social relationships as normatively defined roles ( Merton, 1957 ). Across a range of cultural contexts, well-being is most strongly associated with marriage (and, to a lesser extent, unmarried cohabitation and strength of partnership) (e.g., Wade and Pevalin, 2004 ; Hewitt et al, 2012 ; Tilburg and van der Pas, 2015 ; Rapp and Stauder, 2019 ; Yang and Park, 2019 ; Still, 2020 ; Zhang and Axinn, 2021 ; cf. Musick and Bumpass, 2012 ; Nicolini et al, 2021 ).…”
Section: Which Kinds Of Human Connection Matter For Subjective Well-b...mentioning
confidence: 99%
“…However, when these romantic relationships go through “heartbreak” or “post-relationship grief”, universal life stress occurs that affects the microbiota. Other research highlights that poor-quality affective-sexual relationships can lead to depression [ 42 ], anxiety [ 43 ], fear [ 44 ], anguish [ 45 ], memory disturbances [ 46 ], emotional disorders [ 47 ], environmentally-sensitive physiological impairment (e.g., of central nervous, endocrine, and immune systems) [ 48 ], different somatic symptoms [ 49 ], and even an increase in the tendency to commit suicide in some people [ 50 ]. In addition, there is increased dissatisfaction with the relationship [ 51 ].…”
Section: Introductionmentioning
confidence: 99%